O impacto do capacitismo: A discriminaç\~ao contra pessoas com deficiência que amplia desigualdades - Liliane Cristina Gonçalves Bernardes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The population of people with disabilities in Brazil is estimated at 18.6 million people, corresponding to approximately 8.9% of the population aged 2 years or older. Statistical data indicate significant inequalities in the areas of education and employment, as well as regional disparities between people with and without disabilities, with the former presenting the worst indicators. Ableism, a form of discrimination directed at people with disabilities, is both a cause and a catalyst for these inequalities. This text presents a literature review on this topic, discussing how ableism contributes to the generation and perpetuation of these inequalities.
Keywords: I31; 330; disability; ableism; stigma; public policy; discrimination; inequality